PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN PENERAPAN RANGKAIAN ELEKTRONIKA - Ratna Sari (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2026)
This research was conducted based on learning conditions that are still dominated by conventional approaches with the teacher as the center of learning activities, so that student involvement in the learning process is not optimal. To overcome this problem, the Problem Based Learning (PBL) model is applied which is oriented towards problem-solving activities. This study aims to analyze the differences in learning outcomes between the experimental class and the control class and to determine the effect of the application of the PBL model on student learning outcomes. The method used is a quasi-experimental with a pretest-posttest control group design. The research subjects consisted of 46 students, namely 22 students in the experimental class and 24 students in the control class. Data collection was carried out through pretest and posttest tests to measure learning outcomes in the cognitive domain. Furthermore, the data were analyzed using normality tests, homogeneity tests, Independent Sample T-Test, and N-Gain. The results of the analysis showed that the significance value of the Independent Sample T-Test was 0.043 (p < 0.05), which indicates a significant difference in learning outcomes between the experimental class and the control class. Additionally, the experimental class achieved an N-Gain score of 0.53, categorized as moderate, while the control class achieved a score of 0.27. These findings indicate that the implementation of the Problem-Based Learning (PBL) model has a positive impact and is more effective than conventional learning in improving student learning outcomes.